New Paths of the History of Justice and Security Institutions in Latin America - Barreneche, Osvaldo (2015)
In the research carried out in Latin America, the history of justice, on the one hand, and the history of security or law enforcement institutions, on the other, often failed to find common grounds in terms of focus, approach, problems, methodologies and even historical periods around which they mostly centered. After several years each current’s searching and making contributions on its own, today, a new coincidence takes place within the sphere of Latin American political history, as renewed in turn by recent contributions, which finds in the 19th century the right spot for thematic crossovers. This article focuses around this specific aspect of the field: surveying the thematic contributions and convergence which, within the historiography, signalize a new meeting point. We would like to argue that it is precisely from here that thematic and research lines are developed and that we will witness the next contributions arise from them.